2016
DOI: 10.1002/ece3.1836
|View full text |Cite
|
Sign up to set email alerts
|

Iberian red deer: paraphyletic nature at mtDNAbut nuclear markers support its genetic identity

Abstract: Red deer populations in the Iberian glacial refugium were the main source for postglacial recolonization and subspecific radiation in north‐western Europe. However, the phylogenetic history of Iberian red deer (Cervus elaphus hispanicus) and its relationships with northern European populations remain uncertain. Here, we study DNA sequences at the mitochondrial control region along with STR markers for over 680 specimens from all the main red deer populations in Spain and other west European areas. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 123 publications
(244 reference statements)
2
43
0
Order By: Relevance
“…Growth variations between C. e. hispanicus populations of Badajoz and Lleida could be attributed to their belonging to different lineages (Carranza et al. ); however, we should bear in mind that the existence of different genetic lineages results from natural selection acting on body mass and/or LH traits. Thus, it is also possible that their different habitat and management cause variations in growth.…”
Section: Discussionmentioning
confidence: 99%
“…Growth variations between C. e. hispanicus populations of Badajoz and Lleida could be attributed to their belonging to different lineages (Carranza et al. ); however, we should bear in mind that the existence of different genetic lineages results from natural selection acting on body mass and/or LH traits. Thus, it is also possible that their different habitat and management cause variations in growth.…”
Section: Discussionmentioning
confidence: 99%
“…Calls of red deer hinds were recorded from 10 June 2011 to 27 June 2011 and from 14 June 2012 to 23 June 2012 at the experimental farm of the University of Castilla-La Mancha (Albacete, Spain, 38°57 10 N, 1°47 00 W, 690 m a.s.l.). The population originated in 1994 from 15 male and 50 female Iberian red deer, phylogenetically representing the Western European line according to Skog et al (2009); or the central Iberian-Western European line according to Carranza et al (2016), from a nearby Las Dehesas public game reserve in Alpera (Albacete) and from Cabañeros National Park (Toledo). The animals used in this study were born and kept in four 10 000 m 2 enclosures on an irrigated pasture.…”
Section: Study Site and Subjectsmentioning
confidence: 99%
“…Red deer recolonized Europe after the LGM from this refugium (Meiri et al., ) and, as it has already been suggested by other authors, the genetic glacial composition of the species in this area presented relict foreign haplotypes (Meiri et al., ). At present, Spanish red deer populations can be grouped into two distinct maternal lineages (Sc and Sw) connected to two refugial areas in the Iberian Peninsula during the Würm glacial period (Carranza, Salinas, Andrés, & Pérez‐González, ; Fernández‐García, Carranza, Martínez, & Randi, ). It has been suggested that only one of these lineages (Sc) contributed to the northwestern European postglacial recolonization (Carranza et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, Spanish red deer populations can be grouped into two distinct maternal lineages (Sc and Sw) connected to two refugial areas in the Iberian Peninsula during the Würm glacial period (Carranza, Salinas, Andrés, & Pérez‐González, ; Fernández‐García, Carranza, Martínez, & Randi, ). It has been suggested that only one of these lineages (Sc) contributed to the northwestern European postglacial recolonization (Carranza et al., ).…”
Section: Introductionmentioning
confidence: 99%